2012
DOI: 10.1097/id.0b013e3182746c3d
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Sinus Augmentation Using Ultrasonic Piezoelectric Vibration and Hydraulic Pressure

Abstract: The crestally approached sinus augmentation using ultrasonic piezoelectric vibration and hydraulic pressure is an additional method of maxillary sinus augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Several recent reviews have shown implant survival rates using lateral window 2,5,7 and transcrestal techniques 8,9 for sinus elevation surgery to be more than 95%. Jensen, 7 in a review of 85 studies, reported survival rates for the rough-surfaced implants of 88.6% to 100%.…”
Section: Definition Of Problemmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Several recent reviews have shown implant survival rates using lateral window 2,5,7 and transcrestal techniques 8,9 for sinus elevation surgery to be more than 95%. Jensen, 7 in a review of 85 studies, reported survival rates for the rough-surfaced implants of 88.6% to 100%.…”
Section: Definition Of Problemmentioning
confidence: 99%
“…No experimental studies have been published on the HPISE sinus lift; only clinical studies by a single group of authors are available [37] [38].…”
Section: Hpise Sinus Lift (Silfradent/italy)mentioning
confidence: 99%
“…In such sites, in order to develop sufficient bone to house the implant, osteotomy preparation can include localized indirect, sinus floor elevation using osteotomes [56][57][58][59][60], specialized burs [61] or piezoelectric tips [62]. Particulate mineralized allograft or xenograft particles or autogenous PRP-fibrin clots [63] often are used in these procedures to maximize new bone formation around the implant apex.…”
Section: Managing Socket Anatomymentioning
confidence: 99%